PERBANDINGAN PENERAPAN HUKUM KELUARGA DI DUNIA ISLAM - Nurul Umah, Habibah; Baroroh, Ummul (Moderation | Journal of Islamic Studies Review, 2022)
Family law can be formulated as laws that regulate family relations from the early days of its formation until the end or end of the family. Family law gets the largest portion in the study of Islamic law because almost every country that claims to be an Islamic country or a majority Muslim population or also a Muslim minority country, recognizes the regulations governing family relationships as law that must be applied and always updated according to need. This article makes a comparison of Islamic family law in the Islamic world on “the application of marriage registration” and “the application of the age of marriage” in the Islamic world, for example: “Turkey and Cyplus”, “Lebanon and Israel”, “Egypt and Sudan”, “Tunisia”, “Jordan and Syria”, “Iran and Iraq”, and “Indonesia”. These countries are constantly making efforts to reform and change their family law laws. Each country is very diverse, due to differences in the historical context of the country's history in the life of the nation's people. However, the most important thing from the reform of Muslim family law (Islamic family law) is the provision regarding marriage registration because it has legal consequences, so there is a need for a minimum age limit for marriage and various marriage requirements applied in a country.